Impact of workforce diversity management on job performance of employees in Saudi Arabia: testing the mediating effect of employee engagement and job match / Qamrul Islam and Mnahel Babgi - Islam, Qamrul; Babgi, Mnahel (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
Diversity in the workplace improves an organization's morale and creates efficiency and effectiveness. Effective management of workforce diversity results into resolving employee job issues associated with justice and equality based on differences such as; gender, ethnicity, and cognitive/physical ability, and finally leads to increase in satisfaction and job performance. The purpose of this study was to investigate the influence of workforce diversity management on employee job performance in the Saudi Arabian context, considering the mediating effect of person-job match and employee engagement. The hypotheses were tested on a sample of 327 employees of different service industries in Saudi Arab using the structural equation modelling technique to measure and test the proposed structural relationships. The results confirmed that diversity management was directly related with improvement in job performance. The results also demonstrated the significant mediating effect of job fit and employee engagement between diversity management and job performance relationship. This article contributes to the existing literature by examining both the direct and indirect effect of diversity management on job performance. The findings of this study provide useful information for policymakers and managers to effectively design and implement their workforce diversity so it will improve employees' job fit, engagement and their performance.